Immune cells differentiation in osteoarthritic cartilage damage: friends or foes? - Liu, Mingxiang; Wu, Chaoqun; Wu, Chaofan; Zhou, Zulong; Fang, Run; Liu, Chenfeng; Ning, Rende (Frontiers in Immunology, 2025)
Osteoarthritis (OA) is a chronic disease primarily characterized by degenerative changes in articular cartilage and synovitis, for which there are currently no targeted or curative therapies available in clinical practice. In recent years, the in-depth analysis of OA using single-cell sequencing and immunomics technologies has revealed the presence of multiple immune cell subsets, as well as different differentiation states within the same subset, in OA. Through immune-immune and immune-joint tissue interactions, these cells collectively promote or inhibit the progression of arthritis. This complex immune network, where “friends and foes coexist,” has made targeted therapeutic strategies aimed at directly eliminating immune cells challenging, highlighting the urgent need for a detailed review of the composition, distribution, functional heterogeneity, therapeutic potential, and potential risks of immune subsets within the joint. Additionally, the similarities and differences between OA and rheumatoid arthritis (RA) in terms of diagnosis and immunotherapy need to be precisely understood, in order to draw lessons from or reject RA-based immunotherapies. To this end, this review summarizes the major triggers of inflammation in OA, the differentiation characteristics of key immune cell subsets, and compares the similarities and differences between OA and RA in diagnosis and treatment. It also outlines the current immunomodulatory strategies for OA and their limitations. Furthermore, we provide a detailed and focused discussion on immune cells that act as “friends or foes” in arthritis, covering the M1/M2 polarization of macrophages, functional heterogeneity of neutrophils, unique roles of dendritic cells at different maturation states, the balance between pro-inflammatory T cells and regulatory T cells (Tregs), and the diverse functions of B cells, plasma cells, and regulatory B cells (Bregs) in OA. By interpreting the roles of these immune cells, this review clarifies the dynamic changes and interactions of immune cells in OA joints, providing a theoretical foundation for more precise targeted interventions in future clinical practice.